Welfare and Distributional Impact of Soaring Prices in Europe - Denisa Maria Sologon; Cathal O'Donoghue; Jules Linden; Iryna Kyzyma; Jason Loughrey (Institute of Labor Economics (IZA), 2022)
This paper disentangles the distributional and welfare impact of price changes since the start of the cost of living crisis for a subset of European countries with different welfare regimes and price changes. It decomposes the impact of inflation and measures welfare changes using the compensating variation and equivalent incomes in a cross-national comparative perspective. The impact of inflation depends on good-specific price increases and budget shares. Budget shares for necessities (e.g. food, domestic fuel, electricity) are higher in poorer countries and for poorer people. Higher price growth in these necessities has resulted in higher inflation in poorer countries. Counter to the media narrative, the distributional impact is less substantial than expected. A significant cross-country variability exists, however, in inflation levels, composition and relative rates across the distribution. Similar levels of inflation regressivity result from different interplays between the level and disproportionality of inflation along the income distribution. We quantify the compensating variation of inflation with a relatively small behavioural component due to the preponderance of necessities among the goods with high price changes. An important factor concerning the potential impact on households is the savings rate. Households with already low savings are disproportionally feeling the impact on their expenditure.
Keywords: D12; D31; D60; E31; I30; 330; inflation; distributional effect; welfare effect